Distribution of heavy metals and risk assessment in mine-affected soils after stabilization - Ahn, Yongtae; Hyun-Shik Yun; KALIMUTHU PANDI; Minkyu Ji; Choi Jae Young (Korean Society of Environmental Engineers (KSEE), 2019)
Researchers have been investigated sequential extraction procedures to quantify the chemical status of metals in the solid phase. In this study, three extraction techniques (Tessier, BCR and the Wenzel sequential extraction methods) were applied to fractionate trace (As, Ni, Zn and Cu) and major (Mn and Fe) elements in two different mine-affected soils after stabilization process. Two sites were found to be re-contaminated by heavy metals. Tessier and BCR sequential extraction methods result shows that most of As in DS and YD mine exist residual form, whereas Wenzel sequential extraction method result displays, As in DS and YD mine as partition amorphous Fe and Al oxides, crystalline Fe and Al oxides, and residual form. Keywords: Abandoned mine; Heavy metal; Sequential extraction; Risk assessment
Keywords: Abandoned mine; Heavy metal; Sequential extraction; Risk assessment